READABILITY LEVELS OF READING TEXTS IN “ENGLISH IN FOCUS” BASED ON FLESCH-KINCAID FORMULA - Kuntum Trilestari (Politeknik Negeri Sriwijaya, 2016)
Usually, a teacher uses a textbook when s/he is teaching reading to the students. Every reading text has its own readability. Readability of a textbook accommodates reading learning process because readability is one of instrument for measuring the word difficulty based on an analysis of language variables. Reading text should be readable for the readers. There is a question appears in this area, “what are readability levels of the reading texts in the textbook?”. This descriptive study tried to find out the readability levels of reading texts in “English in Focus” textbook for the eighth graders published by National Education Department (2008) based on Flesch-Kincaid formula. The data was taken from all reading texts in the textbook, and documentary technique was used to find the reading text. Flesch Reading Ease and Flesch-Kincaid Grade Level were used to analyze reading difficulty level and reading grade level of the reading texts. For further detail, this article will discuss the findings of the study.